Rancang Bangun Alat Ukur Monitoring Dan Pengukuran Kontaminasi Tanah (Studi Kasus: Desa Pelangan Kecamatan Sekotong) - Alfina Taurida Alaydrus; Teguh Rifandi; Laili Mardiana; Kasnawi Al Hadi; Suhayat Minardi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
Gold processing waste contains many chemicals compound such as mercury and cyanide, which may help change the physical character of soil. In this study, the temperature, humidity and soil pH has been measured. Measurements of temperature and soil moisture are carried out using SHT11 sensors directly during gold processing. Measurements were carried out around the pond in three different directions. Each direction has 6 points, spaced 5 m apart. Measurements at one point are carried out for 20-21 hours. The measurement results are then mapped to a contour using Surfer-13. Based on the measurement results, obtained temperature values for all points are in the range 25.2-30.3 °C. While the value of soil moisture around 63.8-89.9%, and the soil pH value ranged from 6.8 to 8.1. The mapping results shows the distribution of temperature, humidity and soil pH with almost the same pattern, where the mercury concentration is linear with soil temperature, and soil pH, but non-linear with soil moisture